A survey of joint activities and travel of household members in the Greater Copenhagen Metropolitan Region - Thorhauge, Mikkel; Vuk, Goran; Kaplan, Sigal (Proceedings from the Annual Transport Conference at Aalborg University, 2012)
The traditional approach for modeling transport-related choices in Denmark refers to individual decision makers. However, in daily activities and travel choices individuals function according to the commitments as family members, and thus their choices derive from the welfare needs of other family members. A family-based approach enables to capture intra-household interactions and the priorities of household members in scheduling their daily activities, thus adding to the realism and the predictive strength of transport models. Joint activities and travel occur in order to maximize efficiency and family quality time, within a daily schedule. The current study unveils the joint activity and travel patterns of household members in the Copenhagen area, as part of the ACTUM research project, funded by the Danish Strategic Research Council, for the development of a new generation of activity-based models in Denmark.